Collaborative Wireless Power Transfer in Wireless Rechargeable Sensor Networks. (30th June 2020) - Amin, Azka; Liu, Xi-Hua; Saleem, Muhammad Asim; Henna, Shagufta; Islam, Taseer-ul; Khan, Imran; Uthansakul, Peerapong; Qurashi, Muhammad Zeshan; Mirjavadi, Seyed Sajad; Forsat, Masoud
Abstract : Wireless power transfer techniques to transfer energy have been widely adopted by wireless rechargeable sensor networks (WRSNs). These techniques are aimed at increasing network lifetime by transferring power to end devices. Under these wireless techniques, the incurred charging latency to replenish the sensor nodes is considered as one of the major issues in wireless sensor networks (WSNs). Existing recharging schemes rely on rigid recharging schedules to recharge a WSN deployment using a single global charger. Although these schemes charge devices, they are not on-demand and incur higher charging latency affecting the lifetime of a WSN. This paper proposes a collaborative recharging technique to offload recharging workload to local chargers. Experiment results reveal that the proposed scheme maximizes average network lifetime and has better average charging throughput and charging latency compared to a global charger-based recharging.